2022
DOI: 10.1111/ejn.15835
|View full text |Cite
|
Sign up to set email alerts
|

Impaired spatial navigation and age‐dependent hippocampal synaptic dysfunction are associated with chronic inflammatory response in db/db mice

Abstract: Type 2 diabetes mellitus (T2DM) increases the risk of developing Alzheimer's disease (AD), which has been proposed to be driven by an abnormal neuroinflammatory response affecting cognitive function. However, the impact of T2DM on hippocampal function and synaptic integrity during aging has not been investigated. Here, we investigated the effects of aging in T2DM on ADlike pathology using the leptin receptor-deficient db/db mouse model of T2DM. Our results indicate that adult T2DM mice exhibited impaired spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 128 publications
2
3
0
Order By: Relevance
“…We recognize that although we have contextualized the findings of our metabolomic study in terms of cognitive decline and dementia, the study does not include cognitive function assessments. However, others utilizing the same models at a similar age to the mice in our study have demonstrated cognitive dysfunction [19,20], providing evidence that the db/db model is an appropriate model for T2DM-induced cognitive decline. In addition, while our study characterized the metabolome of the whole brain, there may be region-specific changes induced by T2DM that may be further modified by sex.…”
Section: Study Limitationssupporting
confidence: 67%
See 2 more Smart Citations
“…We recognize that although we have contextualized the findings of our metabolomic study in terms of cognitive decline and dementia, the study does not include cognitive function assessments. However, others utilizing the same models at a similar age to the mice in our study have demonstrated cognitive dysfunction [19,20], providing evidence that the db/db model is an appropriate model for T2DM-induced cognitive decline. In addition, while our study characterized the metabolome of the whole brain, there may be region-specific changes induced by T2DM that may be further modified by sex.…”
Section: Study Limitationssupporting
confidence: 67%
“…We selected 18 weeks of age (4.5 months) for our terminal timepoint. Others have shown that db / db mice will exhibit poorer performance on cognitive tests by this time frame (3–5 months of age) as compared to WT mice [ 19 ]. A flowchart of the experimental procedures can be found in Figure S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of a persistent loop of mutual activation between astrocytes and microglia, subsequently influencing neuronal activity and memory, it is likely that ACN inhibition might be sufficient to interrupt such a vicious cycle, preserving neuronal function. Reduced neuroinflammation can be, indeed, positively associated with the preservation of cognitive abilities we observed both in the AβO-induced and in indACNKO-AD mice, because of the strong association described between glial activation, neuroinflammation, and synaptic plasticity and memory (Al-Onaizi et al, 2022;Amirahmadi et al, 2022;Balducci et al, 2017;Hong et al, 2016;Morris et al, 2013;Sandhu et al, 2022;Zhang et al, 2022).…”
Section: Astroglial Can As a Central Hub Of Neuroinflammation And Hom...supporting
confidence: 60%
“…Mouse cytokine antibody array (Abcam, Cat# ab133995) was used to evaluate the levels of 62 different cytokines in serum samples 23 . 4 samples from Control and LED treated group from both 420 nm & 450nm were used.…”
Section: Cytokine Antibody Arraymentioning
confidence: 99%